Effect of Cold Forming on the High Cycle Fatigue Behaviour of a 27MnCr5 Steel. (2015) - Gerin, B.; Pessard, E.; Morel, F.; Verdu, C.; Mary, A.
Abstract: Cold extrusion is a process commonly used to manufacture drive train components in the automotive industry. Large plastic strains can be applied during this operation (up to 150%) and greatly changes the mechanical properties of the resulting material. This study, part of the ANR project Defisurf focuses on the impact of cold-forging process parameters on the fatigue behavior of steel components. The goal is to decouple the various effects of cold-working by analyzing the material properties and performing fatigue tests. A specific tool has been developed, in collaboration with the Gevelot company, to get original fatigue specimen able to characterize the effect of the manufacturing process on the fatigue behavior. The specimens are extruded from two different initial diameters, giving two different reductions in cross-section of 18% and 75% respectively. These values represent the range of cross-section reduction found in cold-forging: a minimum reduction is always applied, and above 75% reduction the components can be damaged (e.g. tearing). To understand the influence of cold-forging, the following analyses have been undertaken for each condition: mono- tonic tensile properties, microstructure, EBSD, residual stresses, hardness and surface roughness. Simulation of the forming process and microstructural observations of the two batches show that the plastic strain is homogeneous in the specimen section. For both reduction factors, the forming process has a positive effect on the components properties: induced residual stresses in compression and improve hardness and roughness (Ra decreasing). Push pull and plane bending fatigue tests show that the fatigue strength is about 30% higher for the high wrought batch. Residual stresses are not relaxed by the applied fatigue loads. SEM observations of the fatigue failure surfaces, for both extrusion condi- tions, show that there is no inclusion or surface defect at the initiation site. All investigations show that strain hardening is the principal material parameter responsible for the increase in fatigue strength.